The Effect of Ethanol-Diesel Blends on The Performance of A Direct Injection Diesel Engine - Arifin Nur; Yanuandri Putrasari; Iman Kartolaksono Reksowardojo (National Research and Innovation Agency, 2012)
The experiment was conducted on a conventional direct injection diesel engine. Performance test was carried out to evaluate the performance and emission characteristics of a conventional diesel engine that operates on ethanol-diesel blends. The test procedure was performed by coupling the diesel engine on the eddy current dynamometer. Fuel consumption was measured using the AVL Fuel Balance, and a hotwire anemometer was used to measure the air consumption. Some of the emission test devices were mounted on the exhaust pipe. The test of fuel variations started from 100% diesel fuel (D100) to 2.5% (DE2.5), 5% (DE5), 7.5% (DE7.5), and 10% (DE10) ethanol additions. Performance test was conducted at 1500 rpm with load variations from 0 to 60 Nm by increasing the load on each level by 10 Nm. The addition of 5% ethanol to diesel (DE5) increased the average pressure of combustion chamber indication to 48% as well as reduced the specific fuel consumption to 9.5%. There were better exhaust emission characteristics at this mixture ratio than diesel engine which used pure diesel fuel (D100), the reduction of CO to 37%, HC to 44% and opacity to 15.9%.